Identification and Characterization of MicroRNAs in Macaca fascicularis by EST Analysis - Yang, Hao (Hindawi Publishing Corporation, 2012)
MicroRNAs (miRNAs) are small noncoding RNAs which repress gene expression at the posttranscriptional level. In this study, an expressed sequence tag (EST)-based combined method was applied for the detection of miRNAs in Macaca fascicularis which is used as a model animal extensively in medical experiments, particularly those involved with neuroscience and disease. Initially, previously known miRNA sequences from metazoans were used to blast with the EST databases of Macaca fascicularis, and then a range of filtering criteria was conducted to remove some pseudo ones. At last a total of 8 novel conserved miRNAs were identified; their functions were further predicted and analyzed. Together, our study provides insight into miRNAs and their functions in Macaca fascicularis, indicating that the EST analysis is an efficient and affordable alternative approach for identifying novel miRNA candidates.